MENINGKATKAN DAYA TARIK PEMBELAJARAN INFORMATIKA MELALUI DESAIN VISUAL DENGAN CANVA DI SMA NEGERI 1 BRINGIN KABUPATEN SEMARANG - Wismarini, Theresia Dwiati; Murti, Hari; Lestariningsih, Endang; Redjeki, Rara Sriartati; Hartono, Budi; Anwar, Sariyun Naja; Lusiana, Veronica; Ardhianto, Eka (Intimas, 2025)
The rapid development of information technology requires teachers to present learning materials in a creative and visual manner. Informatics teachers at SMA Bringin face challenges in creating visually engaging teaching materials due to limited graphic design knowledge, which results in low student engagement and less effective delivery of content. To address this issue, a community service activity in the form of Canva training for informatics teachers at SMA Bringin was conducted. This activity followed a participatory and hands-on approach (learning by doing). The training took place over two days in the school's computer lab and was attended by 15 informatics teachers as well as several other subject teachers. Evaluation results showed 35% improvement in participants' understanding of Canva, based on a comparison of pre-test and post-test scores. Participants also displayed high creativity and enhanced visual skills in their final tasks, which involved creating educational materials using Canva. The satisfaction survey revealed that 93% of participants found the training highly beneficial and expressed their intention to adopt Canva in regular teaching. Overall, this training successfully improved the digital literacy of teachers, particularly in designing visual teaching media using Canva. Participants provided feedback suggest the organization of follow-up training focusing on animation or interactive video-based learning.